2013
DOI: 10.1371/journal.pone.0062208
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Inflammation in Mice Is Improved by Cigarette Smoke through iNKT Cells Recruitment

Abstract: Cigarette smoke (CS) protects against intestinal inflammation during ulcerative colitis. Immunoregulatory mechanisms sustaining this effect remain unknown. The aim of this study was to assess the effects of CS on experimental colitis and to characterize the intestinal inflammatory response at the cellular and molecular levels. Using the InExpose® System, a smoking device accurately reproducing human smoking habit, we pre-exposed C57BL/6 mice for 2 weeks to CS, and then we induced colitis by administration of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…This tumour formation was associated with inhibition of cellular apoptosis and supported by increased angiogenesis. As a possible explanation for this discrepancy, this study used Balb/c mice while the protective effects of CS [22] were observed in C57BL/6 mice. Opposite responses in Balb/c mice, compared with C57BL/6 and other mouse strains, were also reported for other chemical inducers of IBD [67].…”
Section: Inhalation Studies Investigating the Effect Of Cs In Rodent mentioning
confidence: 96%
See 2 more Smart Citations
“…This tumour formation was associated with inhibition of cellular apoptosis and supported by increased angiogenesis. As a possible explanation for this discrepancy, this study used Balb/c mice while the protective effects of CS [22] were observed in C57BL/6 mice. Opposite responses in Balb/c mice, compared with C57BL/6 and other mouse strains, were also reported for other chemical inducers of IBD [67].…”
Section: Inhalation Studies Investigating the Effect Of Cs In Rodent mentioning
confidence: 96%
“…In contrast to its effects in CD rodent models, CS exposure for 2 weeks decreased UC-like inflammation in an acute DSS-induced colitis model in mice [22]. Montbarbon et al showed a significant decrease in macroscopic and histological colon damage, as well as in colonic proinflammatory cytokine expression, in DSS-exposed mice after CS inhalation.…”
Section: Inhalation Studies Investigating the Effect Of Cs In Rodent mentioning
confidence: 97%
See 1 more Smart Citation
“…28 In contrast, the lamina propria lymphocytes, which are scattered throughout the lamina propria underneath the epithelial layer, are more diverse in their cellular composition and resemble more those of other lymphatic organs. 29 iNKT cells can be detected in the mouse intestine at frequencies only slightly lower than in other peripheral organs, like the spleen and lymph nodes (stomach, 30 small intestine, [31][32][33] large intestine [33][34][35][36][37] ). Approximately 65% (BALB/c mice) to 85% (C57BL/6 mice) of intestinal iNKT cells are NKT1 cells, with the rest largely being NKT2 cells, and no differences in this distribution were noted for IELs versus lamina propria lymphocytes.…”
Section: (3) Mucus Production and Glycosylationmentioning
confidence: 96%
“…164,199 IBD and the microbiome IBD is a group of disorders characterized by chronic inflammation of the gastrointestinal tract, of which the two main disease manifestations, ulcerative colitis (UC) and Crohn's disease (CD), each have distinctive clinical and pathological features. [200][201][202][203] Both CD and UC result from a complex interplay among environmental factors, genetics, and intestinal microbiota composition. 204,205 The important role of the microbiome in IBD pathogenesis has been elucidated by a study where germ-free animals showed less inflammation than controls in response to dextran sulfate sodium (DSS)-induced colitis.…”
Section: 110178mentioning
confidence: 99%